Group Care in the first 1000 days: implementation and process evaluation of contextually adapted antenatal and postnatal group care targeting diverse vulnerable populations in high-, middle- and low-resource settings - Nele Martens; Mathilde R. Crone; Ashna Hindori-Mohangoo; Manodj Hindori; Ria Reis; Ilir S. Hoxha; Jedidia Abanga; Shanaaz Matthews; Lizette Berry; Rianne M. J. J. van der Kleij; M. Elske van den Akker-van Marle; Astrid van Damme; et al. (Implementation Science Communications, 2022)
Abstract Background Group care (GC) improves the quality of maternity care, stimulates women’s participation in their own care and facilitates growth of women’s social support networks. There is an urgent need to identify and disseminate the best mechanisms for implementing GC in ways that are feasible, context appropriate and sustainable. This protocol presents the aims and methods of an innovative implementation research project entitled Group Care in the first 1000 days (GC_1000), which addresses this need. Aims The aim of GC_1000 is to co-create and disseminate evidence-based implementation strategies and tools to support successful implementation and scale-up of GC in health systems throughout the world, with particular attention to the needs of ‘vulnerable’ populations. Methods By working through five inter-related work packages, each with specific tasks, objectives and deliverables, the global research team will systematically examine and document the implementation and scale-up processes of antenatal and postnatal GC in seven different countries. The GC_1000 project is grounded theoretically in the consolidated framework for implementation research (CFIR), while the process evaluation is guided by ‘Realistic Evaluation’ principles. Data are gathered across all research phases and analysis at each stage is synthesized to develop Context-Intervention-Mechanism-Outcome configurations. Discussion GC_1000 will generate evidence-based knowledge about the integration of complex interventions into diverse health care systems. The 4-year project also will pave the way for sustained implementation of GC, significantly benefitting populations with adverse pregnancy and birthing experiences as well as poor outcomes.